Presence of Senecio sylvaticus L. (Asteraceae) in Turkey - Tunçkol, Bilge; Yaşayacak, Hasan; Aksoy, Necmi (Biodiversity: Research and Conservation, 2015)
The annual plant Senecio sylvaticus L. (Asteraceae) is regarded as a doubtfully recorded in Turkey. It has not been collected in the country since the first report of its occurrence in the north eastern Black Sea Region in 1875. This paper reconfirms the occurrence of Senecio sylvaticus in Turkey. New specimens were collected from the Ereğli and Alaplı regions (Zonguldak province, NW Turkey) in 2014. The species description, distribution maps and photographs are given.